GLONASS AS A TOOL TO ENSURE THE SAFETY OF TRANSPORTATION OF DANGEROUS GOODS - A. Ochkalova (Вестник университета, 2016)
The article describes the definition of dangerous goods, shows the reasons for the increased control over the transportation of such kind of goods and special security measures, gives the peculiarities of satellite navigation systems, the algorithm of implementation of the global navigation tracking system in practice, and shows a need for further measures to ensure safety transportation of dangerous goods.